2016
DOI: 10.1007/s13277-016-5219-3
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-451 inhibits glioma cell proliferation and invasion by downregulating glucose transporter 1

Abstract: MicroRNAs play an important role in tumor development and progression. Tumor growth is closely associated with glucose metabolism. Specifically, tumor cells produce energy (ATP) under aerobic and anaerobic conditions through glycolysis and metabolites, such as lactic acid and ATP, as a result of the Warburg effect. However, the transport of glucose into cells depends on protein transporters in the cell membrane. Therefore, this area has recently become a topic of interest for research on targeted cancer therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Differential expression of specific microRNAs (miRNAs or miRs) in gliomas compared with normal tissues has previously been reported (9)(10)(11). miRNAs are single-stranded, highly conserved non-coding RNA molecules (19)(20)(21)(22)(23)(24)(25) nucleotides in length) that regulate the expression of >60% of human genes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Differential expression of specific microRNAs (miRNAs or miRs) in gliomas compared with normal tissues has previously been reported (9)(10)(11). miRNAs are single-stranded, highly conserved non-coding RNA molecules (19)(20)(21)(22)(23)(24)(25) nucleotides in length) that regulate the expression of >60% of human genes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose as well as glutamine are important substrates for glycolysis and glutaminolysis, which are important to glioma development and a more aggressive behavior through regulation of the cell cycle at distinct stages (Colombo et al 2011;Yalcin et al 2014;Zhao et al 2017). It has been shown that down-regulation of glucose transporter 1 by microRNA miR-451 inhibits the glucose metabolism and proliferation as well as invasion of glioma cells (Guo et al 2016).…”
mentioning
confidence: 99%
“…It has been reported that miR-451 was directly involved in the development of drug resistance of several types of cancers, such as non-small-cell lung cancer (NSCLC), colon carcinoma and glioblastoma. 17 , 18 , 19 Although these studies have showed that the potential role of miR-451 in chemoresistance in human cancer, the function of miR-451 in BC remains poorly understood.…”
mentioning
confidence: 99%